2012
DOI: 10.4103/0970-9290.100433
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of deciduous teeth emergence with physical growth

Abstract: All anthropometric parameters showed relationship with the number of teeth at different levels. Although weight showed influence on the number of teeth emerged, it was less significant than height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“… 4 Tooth eruption recognized as an aspect of human growth and development could possibly be influenced by number of factors that can be both physiological and pathological like growth, caries, malnutrition, genetics, etc. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 4 Tooth eruption recognized as an aspect of human growth and development could possibly be influenced by number of factors that can be both physiological and pathological like growth, caries, malnutrition, genetics, etc. 5 …”
Section: Introductionmentioning
confidence: 99%
“…The presence of 16 or more primary teeth occurred when birth weight and weight at the 18-month-old health examination were greater, height at the 18-month-old health examination was higher, and fused teeth were fewer at the 18-month-old health examination. Soliman et al 5 reported positive correlations between anthropometric measurements (height and weight) and the number of emerged primary teeth in Egyptian infants whose ages ranged from 4 to 36 months. The positive correlation was observed in 18-month-old infants, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 As for the 1990s and 2000s, several studies on primary tooth emergence timing were reported for several countries, including far-east Asian countries. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 Woodroffe et al 12 observed that overall emergence patterns of primary anterior teeth were generally later than in the ones that had been previously reported for Australian children. However, there have been only a few similar reports on primary tooth emergence in Japanese children after the 1990s.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations